Detection of License Plates of Vehicles - Wanniarachchi, W. K. I. L.; Sonnadara, D.U.J.; Jayananda, M. K. (My University, 2007)
This paper presents an image processing approach for the detection of the vehicle license plate area in digitized photographic images. The algorithm takes a raster image of the rear view of a vehicle as input and yields the segment of the photograph that contains the plate as the output. The developed algorithm is based on three basic processing stages; yellow regions extraction, dilation of yellow regions and extraction of the plate region. The performance of the developed algorithm has been tested on a set of real images of vehicles. Preliminary tests show that the algorithm performs quite well in accurately locating the license plates (with 97% efficiency). The results of this work can be extended for the automatic detection and recognition of vehicle license plates for vehicle identification.
Keywords: Image processing; Vehicle detection